Preparation method and application of antibacterial nano composite material
An antibacterial nanocomposite material is prepared through a combination of graphite phase carbon nitride doped with modified ceria and chitosan. Visible light excitation is used to generate active free radicals, which solves the problem of complex preparation and difficult removal of antibacterial materials in the existing technology. The problem of mature biofilms achieves efficient and economical antibacterial effects.
Patent Information
- Application Number
- CN202411477956.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, antibacterial nanomaterials are complex in preparation, limited in practical application range, and difficult to effectively remove mature biological membranes, and the price is relatively high.
By doping graphite-phase carbon nitride with modified ceria and combining chitosan as a dispersant, an antibacterial nanocomposite material is prepared, which uses visible light excitation to generate active free radicals to attack bacteria and biofilms.
An antibacterial nanocomposite material with simple preparation, easily available raw materials, and wide range of applications has been realized, which can effectively inhibit and kill bacteria, remove and inhibit bacterial biofilm, and has a low cost.
Smart Images

Figure CN119344330A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a preparation method and application of an antibacterial nanocomposite material. Background Art
[0002] Foodborne pathogens easily form structured bacterial communities, produce biofilms, and cause food safety issues, which have attracted social attention. Natural polysaccharides and nanoparticle metals have good antibacterial properties and are often used to remove pathogens and reduce the harm caused by their biofilms.
[0003] In the prior art, nanozymes are mostly composed of multiple catalytic materials, which are excited at a specific infrared wavelength to produce active oxygen to resist biofilms. However, these methods generally have the problem of complex material preparation and limited practical application range. At the same time, for mature biofilms that are difficult to remove, the currently commonly used nanoparticles such as nanosilver and nanocopper oxide are difficult to achieve the ideal removal effect, and the price is relatively expensive. Therefore, it is necessary to develop a nanocomposite material with a simple preparation method, easy to obtain raw material sources, a wide range of practical applications, and better antibacterial and mature biofilm removal effects. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention provides a preparation method and application of an antibacterial nanocomposite material.
[0005] The first object of the present invention is to provide a method for preparing an antibacterial nanocomposite material.
[0006] The second object of the present invention is to provide an antibacterial nanocomposite material obtained according to the preparation method.
[0007] The third object of the present invention is to provide the use of the antibacterial nanocomposite material in in vitro bacteriostasis and / or in vitro bactericidal activity.
[0008] The fourth object of the present invention is to provide the use of the antibacterial nanocomposite material in the preparation of antibacterial products.
[0009] The fifth object of the present invention is to provide the use of the antibacterial nanocomposite material in preparing products for removing and / or inhibiting bacterial biofilm.
[0010] The sixth object of the present invention is to provide an antibacterial composition.
[0011] The seventh object of the present invention is to provide an antibacterial agent.
[0012] In order to achieve the above object, the present invention is implemented by the following scheme:
[0013] The present invention dopes and modifies cerium dioxide with graphite phase carbon nitride to obtain an antibacterial nanocomposite material, and realizes the utilization of visible light. In addition, chitosan is used as a dispersant to mix and react with the obtained antibacterial nanocomposite material to obtain a chitosan-antibacterial nanocomposite material. Under the excitation of visible light, the modified cerium dioxide is catalyzed to generate active free radical ions, which attack bacteria and their biofilm structures, and finally inhibit the formation of biofilms and eliminate mature biofilms.
[0014] A method for preparing an antibacterial nanocomposite material, wherein the antibacterial nanocomposite material is synthesized by using graphite phase carbon nitride and cerium salt through a hydrothermal method or a template method;
[0015] The hydrothermal method comprises the following steps: after the graphite phase carbon nitride and cerium dioxide are fully dispersed, a sufficient hydrothermal reaction is carried out in a closed container to obtain; the mass ratio of the graphite phase carbon nitride to the cerium dioxide is 1:(0.5-3); the conditions of the hydrothermal reaction include: the temperature is 100°C-150°C; the antibacterial nanocomposite material synthesized by the hydrothermal method is g-C3N4 / CeO2-HT;
[0016] The template method comprises the following steps: after the graphite phase carbon nitride is fully combined with the cerium nitrate solution, the solid-liquid separation is carried out, the liquid is collected, the solvent of the liquid is removed to obtain a precipitate, and the precipitate is fully calcined to obtain; the molar ratio of cerium in the cerium nitrate to the graphite phase carbon nitride is (0.04-0.10):1; the calcination conditions include: the calcination temperature is 500°C-600°C; the antibacterial nanocomposite material synthesized by the template method is g-C3N4 / CeO2-MD.
[0017] Preferably, the graphite phase carbon nitride is synthesized by high temperature thermal polycondensation of melamine.
[0018] Preferably, in the hydrothermal method, the mass ratio of the graphite-phase carbon nitride to the cerium dioxide is 1:0.5, 1:1, 1:1.5, 1:2 or 1:3.
[0019] More preferably, in the hydrothermal method, the mass ratio of the graphite-phase carbon nitride to the cerium dioxide is 1:1.
[0020] Preferably, in the hydrothermal method, the conditions of the hydrothermal reaction also include: the reaction time is 16h to 20h.
[0021] More preferably, in the hydrothermal method, the conditions of the hydrothermal reaction include: 100° C. for 20 h, 120° C. for 18 h, or 150° C. for 16 h.
[0022] Further preferably, in the hydrothermal method, the hydrothermal reaction condition is 120° C. for 18 hours.
[0023] Preferably, in the hydrothermal method, the cerium dioxide is first fully calcined and then fully dispersed with the graphite phase carbon nitride.
[0024] Preferably, in the hydrothermal method, the graphite carbon nitride and the cerium dioxide are fully dispersed in water.
[0025] Preferably, in the hydrothermal method, the method of fully dispersing includes stirring and ultrasound.
[0026] Preferably, in the hydrothermal method, the closed container includes a reaction kettle.
[0027] More preferably, the reactor is a high-pressure reactor.
[0028] Preferably, in the hydrothermal method, after the hydrothermal reaction is completed, the obtained reaction product is purified.
[0029] More preferably, the purification method comprises: washing, centrifugation and drying.
[0030] Preferably, in the template method, the molar ratio of cerium in the cerium nitrate to the graphite-phase carbon nitride is 0.04:1, 0.06:1, 0.08:1 or 0.10:1.
[0031] More preferably, in the template method, the molar ratio of cerium in the cerium nitrate to the graphite-phase carbon nitride is 0.08:1.
[0032] Preferably, in the template method, the calcination conditions further include: the calcination time is 1 hour to 3 hours.
[0033] More preferably, in the template method, the calcination conditions include: 500° C. for 3 h, 550° C. for 2 h, or 600° C. for 1 h.
[0034] Further preferably, in the hydrothermal method, the hydrothermal reaction condition is 550° C. for 2 h.
[0035] More preferably, in the template method, the method of fully combining the graphite phase carbon nitride with the cerium nitrate solution comprises the following steps: fully mixing the graphite phase carbon nitride with the cerium nitrate solution and then allowing them to stand.
[0036] Preferably, in the template method, the solid-liquid separation method includes filtration.
[0037] Preferably, in the template method, the method of removing the solvent of the liquid comprises drying.
[0038] Preferably, in the template method, the precipitate is cooled after being fully calcined.
[0039] The antibacterial nanocomposite material obtained by any of the preparation methods should also be within the protection scope of the present invention.
[0040] The application of the antibacterial nanocomposite material in in vitro bactericidal and / or in vitro bacteriostasis should also be within the protection scope of the present invention.
[0041] The application of the antibacterial nanocomposite material in the preparation of antibacterial products should also be within the protection scope of the present invention.
[0042] The use of the antibacterial nanocomposite material in the preparation of products for removing and / or inhibiting bacterial biofilms should also be within the protection scope of the present invention.
[0043] Preferably, the bacterial biofilm comprises a bacterial mature biofilm.
[0044] Preferably, the bacteria include Staphylococcus aureus and / or Escherichia coli.
[0045] An antibacterial composition comprises the antibacterial nanocomposite material and chitosan.
[0046] Preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.5).
[0047] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.2).
[0048] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01, 1:0.1, 1:0.2 or 1:0.5.
[0049] Further preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01.
[0050] Preferably, the antibacterial nanocomposite material is synthesized by the template method.
[0051] The use of the antibacterial composition in in vitro bacteriostasis and / or in vitro bactericidal treatment should also be within the protection scope of the present invention.
[0052] The use of the antibacterial composition in the preparation of antibacterial products should also be within the protection scope of the present invention.
[0053] The use of the antibacterial composition in the preparation of products for removing and / or inhibiting bacterial biofilms should also be within the protection scope of the present invention.
[0054] Preferably, the bacterial biofilm comprises a bacterial mature biofilm.
[0055] Preferably, the bacteria include Staphylococcus aureus and / or Escherichia coli.
[0056] An antibacterial agent comprises the antibacterial nanocomposite material or the antibacterial composition, wherein the antibacterial composition comprises the antibacterial nanocomposite material and chitosan.
[0057] Preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.5).
[0058] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.2).
[0059] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01, 1:0.1, 1:0.2 or 1:0.5.
[0060] Further preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01.
[0061] A method for preparing an antibacterial agent comprises the following steps: fully mixing chitosan and the antibacterial nanocomposite material in an acetic acid solution at a mass ratio of 1:(0.01-0.5).
[0062] Preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.5).
[0063] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.2).
[0064] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01, 1:0.1, 1:0.2 or 1:0.5.
[0065] Further preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01.
[0066] Preferably, the concentration of the acetic acid solution is 1% (v / v) to 2% (v / v).
[0067] Preferably, the mass volume ratio of the chitosan to the acetic acid solution is (1-2) g:100 mL.
[0068] More preferably, the mass volume ratio of the chitosan to the acetic acid solution is 1 g:100 mL.
[0069] The antibacterial agent prepared by any of the methods described should also be within the protection scope of the present invention.
[0070] A method for preparing an antibacterial film comprises the following steps: fully mixing chitosan and the antibacterial nanocomposite material in an acetic acid solution at a mass ratio of 1:(0.01-0.5), casting, and fully drying.
[0071] Preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.5).
[0072] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:(0.01-0.2).
[0073] More preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01, 1:0.1, 1:0.2 or 1:0.5.
[0074] Further preferably, the mass ratio of the chitosan to the antibacterial nanocomposite material is 1:0.01.
[0075] Preferably, the concentration of the acetic acid solution is 1% (v / v) to 2% (v / v).
[0076] Preferably, the mass volume ratio of the chitosan to the acetic acid solution is (1-2) g:100 mL.
[0077] More preferably, the mass volume ratio of the chitosan to the acetic acid solution is 1 g:100 mL.
[0078] Preferably, the drying method comprises oven drying.
[0079] Compared with the prior art, the present invention has the following beneficial effects:
[0080] The antibacterial nanocomposite material provided by the present invention not only has a simple preparation method, but also has more advantages than traditional precious metal antibacterial nanomaterials, such as easy availability of raw materials and low cost, strong light absorption ability, and can effectively inhibit and kill Gram-positive bacteria and Gram-negative bacteria under a variety of lighting conditions, and can more effectively remove and inhibit bacterial biofilms. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 Characterization of g-C3N4, CeO2 in Application Example 1, g-C3N4 / CeO2-HT prepared in Example 3, and g-C3N4 / CeO2-MD prepared in Example 11; A is the Fourier transform infrared spectrum; B is the UV-visible diffuse reflectance spectrum; C is the Tauc relationship diagram.
[0082] Figure 2This is the SEM characterization of the CS / g-C3N4 / CeO2-HT film in Application Example 1; A to D are the SEM images of the CS / g-C3N4 / CeO2-HT films prepared from the suspensions used in Examples 15 to 18, respectively.
[0083] Figure 3 It is the element distribution diagram of the CS / g-C3N4 / CeO2-HT film in Application Example 1; A-1 to A-4 are respectively the carbon, nitrogen, oxygen and cerium mapping diagrams of the CS / g-C3N4 / CeO2-HT film whose suspension is prepared by Example 15; B-1 to B-4 are respectively the carbon, nitrogen, oxygen and cerium mapping diagrams of the CS / g-C3N4 / CeO2-HT film whose suspension is prepared by Example 16; C-1 to C-4 are respectively the carbon, nitrogen, oxygen and cerium mapping diagrams of the CS / g-C3N4 / CeO2-HT film whose suspension is prepared by Example 17; D-1 to D-4 are respectively the carbon, nitrogen, oxygen and cerium mapping diagrams of the CS / g-C3N4 / CeO2-HT film whose suspension is prepared by Example 18.
[0084] Figure 4 The CS / g-C3N4 / CeO2-MD film prepared by Example 22 using the suspension used for HRTEM characterization in Application Example 1; A is the HR-TEM image; B is a local enlarged image of the CeO2 lattice fringes in A.
[0085] Figure 5 are the antibacterial rate of the antibacterial nanocomposite material in Application Example 2 and its effect on the total amount of mature biofilm and its removal rate; A is the antibacterial rate of g-C3N4 / CeO2-HT prepared in Examples 2 to 8 against Staphylococcus aureus (S.aureus) 10071; B is the antibacterial rate of g-C3N4 / CeO2-MD prepared in Examples 9 to 14 against Staphylococcus aureus (S.aureus) 10071.
[0086] Figure 6 is the antibacterial rate of the antibacterial nanoparticle-chitosan film under different conditions in Application Example 2; A is the antibacterial rate of the CS / g-C3N4 / CeO2-MD film whose suspension is prepared by Example 20 against Escherichia coli (O78), Staphylococcus aureus (S.aureus) 10071 and 10008 in the absence of light or under ultraviolet light; B is the antibacterial rate of the CS / g-C3N4 / CeO2-HT film material of Examples 11 to 14 against Escherichia coli (O78), Staphylococcus aureus (S.aureus) 10071 and 10008 under normal light conditions.
[0087] Figure 7 The figures are the effects of g-C3N4 / CeO2-HT prepared in Example 3 and g-C3N4 / CeO2-MD prepared in Example 11 on bacterial biofilm under different conditions in Application Example 2; A is the effect of direct sampling, direct sampling + UV light, sample addition without culture, and sample addition without culture + UV light on the total amount of biofilm of Staphylococcus aureus (S.aureus) 10071 and 10008 determined by CV method; B is the statistical results of the removal rate of biofilm of Staphylococcus aureus (S.aureus) 10071 and 10008 under direct sampling, direct sampling + UV light, sample addition without culture, and sample addition without culture + UV light.
[0088] Figure 8 The figures are the effects of g-C3N4 / CeO2-HT prepared in Example 3 and g-C3N4 / CeO2-MD prepared in Example 11 and the antibacterial nanoparticle-chitosan composite solutions of Examples 15 to 22 on bacterial biofilms under different direct sampling conditions in Application Example 2; A is the OD value result of the total amount of Staphylococcus aureus (S.aureus) 10071 biofilm determined by CV method under direct sampling and direct sampling + visible light conditions; B is the statistical result of the clearance rate of Staphylococcus aureus (S.aureus) 10071 biofilm under direct sampling and direct sampling + visible light conditions; C is the OD value result of the total amount of Staphylococcus aureus (S.aureus) 10008 biofilm determined by CV method under direct sampling and direct sampling + visible light conditions; D is the statistical result of the clearance rate of Staphylococcus aureus (S.aureus) 10008 biofilm under direct sampling and direct sampling + visible light conditions.
[0089] Fig. 9 The figures are the effects of g-C3N4 / CeO2-HT prepared in Example 3 and g-C3N4 / CeO2-MD prepared in Example 11 and the antibacterial nanoparticle-chitosan composite solutions of Examples 15 to 22 on bacterial biofilms under different conditions of removing the culture medium and adding the sample in Example 2; A is the OD value result of the total amount of Staphylococcus aureus (S.aureus) 10071 biofilm under the conditions of removing the culture medium and adding the sample in the visible light by CV method; B is the statistical result of the clearance rate of Staphylococcus aureus (S.aureus) 10071 biofilm under the conditions of removing the culture medium and adding the sample in the visible light by CV method; C is the OD value result of the total amount of Staphylococcus aureus (S.aureus) 10008 biofilm under the conditions of removing the culture medium and adding the sample in the visible light by CV method; D is the statistical result of the clearance rate of Staphylococcus aureus (S.aureus) 10008 biofilm under the conditions of removing the culture medium and adding the sample in the visible light by CV method.
[0090] Fig.10The figures show the effect of nano-Ag particles (positive control) on bacterial biofilm under different sample addition conditions in Application Example 2; A is the OD value result of the total amount of biofilm of Staphylococcus aureus (S.aureus) 10071 determined by CV method; B is the statistical result of the clearance rate of biofilm of Staphylococcus aureus (S.aureus) 10071; C is the OD value result of the total amount of biofilm of Staphylococcus aureus (S.aureus) 10008 determined by CV method; D is the statistical result of the clearance rate of biofilm of Staphylococcus aureus (S.aureus) 10008. DETAILED DESCRIPTION
[0091] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0092] Example 1 Synthesis of graphite phase carbon nitride
[0093] Referring to the prior art "Liu Chengcan's "Modification of Graphite-like Carbon Nitride and Its Piezoelectric Catalytic Performance"", "Ma Wenqi's "Piezoelectric Photocatalytic Degradation Performance of Graphite-like Carbon Nitride-based Composite Materials" and other literatures, graphite phase carbon nitride was synthesized, specifically: at a temperature of 550°C and a time of 2h, 5g of melamine was used as the base material to synthesize graphite phase carbon nitride (g-C3N4, CAS No.: 143334-20-7) by a high-temperature thermal polycondensation method.
[0094] Example 2 Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0095] 0.1 g of cerium dioxide (CeO2, CAS No.: 23322-64-7) particles were placed in a muffle furnace, calcined at 300°C for 4 hours, cooled to 25°C, and then mixed with 0.2 g of g-C3N4 synthesized in Example 1 (i.e., the mass ratio of g-C3N4 to CeO2 is 2:1) and 0.1 L of distilled water, and then stirred with a magnetic stirrer for 0.5 hours to obtain a mixed solution; after the mixed solution was ultrasonically treated at a power of 600 W for 0.5 hours, it was transferred to a polyfluoro lined container, and then loaded into a high-pressure reactor, placed in a constant temperature forced air drying oven for hydrothermal reaction at 120°C for 18 hours, and cooled to room temperature; the reactants were collected, washed with ethanol, and centrifuged and dried to obtain an antibacterial nanocomposite material, which was recorded as graphite phase carbon nitride / cerium dioxide-hydrothermal method, i.e., g-C3N4 / CeO2-HT.
[0096] Example 3 Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0097] 0.1 g of CeO2 particles and 0.1 g of g-C3N4 synthesized in Example 1 (i.e., the mass ratio of g-C3N4 to CeO2 is 1:1) were mixed according to the synthesis method in Example 2 to obtain g-C3N4 / CeO2-HT.
[0098] Example 4: Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0099] 0.15 g of CeO2 particles and 0.1 g of g-C3N4 synthesized in Example 1 (i.e., the mass ratio of g-C3N4 to CeO2 is 1:1.5) were mixed according to the synthesis method in Example 2 to obtain g-C3N4 / CeO2-HT.
[0100] Example 5: Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0101] 0.2 g of CeO2 particles and 0.1 g of g-C3N4 synthesized in Example 1 (i.e., the mass ratio of g-C3N4 to CeO2 is 1:2) were mixed according to the synthesis method in Example 2 to obtain g-C3N4 / CeO2-HT.
[0102] Example 6 Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0103] 0.3 g of CeO2 particles and 0.1 g of g-C3N4 synthesized in Example 1 (i.e., the mass ratio of g-C3N4 to CeO2 is 1:3) were mixed according to the synthesis method in Example 2 to obtain g-C3N4 / CeO2-HT.
[0104] Example 7 Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0105] It is basically the same as Example 2, except that: it is placed in a constant temperature forced air drying oven for hydrothermal reaction at 100°C for 20 hours to obtain g-C3N4 / CeO2-HT.
[0106] Example 8: Synthesis of antibacterial nanocomposite materials by hydrothermal method
[0107] It is basically the same as Example 2, except that: it is placed in a constant temperature forced air drying oven for hydrothermal reaction at 150°C for 16 hours to obtain g-C3N4 / CeO2-HT.
[0108] Example 9 Synthesis of antibacterial nanocomposite materials by template method
[0109] 0.2L 3.47g / mol cerium nitrate solution (Ce(NO3)3, CAS No.: 10294-41-4) and 4g g-C3N4 synthesized in Example 1 (i.e., the molar ratio of g-C3N4 to Ce is 0.04:1) are fully mixed and soaked for 6h; filtered, the filtrate is taken, placed in a constant temperature forced air drying oven at 60°C, dried for 12h, collected and then calcined at 550°C in a muffle furnace for 2h (Ce(NO3)3 is converted into CeO2 at high temperature), and after fully cooling to 25°C, an antibacterial nanocomposite material is obtained, which is recorded as graphite phase carbon nitride / cerium dioxide-template method, i.e., g-C3N4 / CeO2-MD.
[0110] Example 10 Synthesis of antibacterial nanocomposite materials by template method
[0111] 0.2L of 5.21g / mol Ce(NO3)3 solution and 4g of g-C3N4 synthesized in Example 1 (ie, the molar ratio of g-C3N4 to Ce is 0.06:1) were added according to the synthesis method in Example 7 to prepare g-C3N4 / CeO2-MD.
[0112] Example 11 Synthesis of antibacterial nanocomposite materials by template method
[0113] 0.2L of 6.95g / mol Ce(NO3)3 solution and 4g of g-C3N4 synthesized in Example 1 (ie, the molar ratio of g-C3N4 to Ce is 0.08:1) were mixed according to the synthesis method in Example 7 to prepare g-C3N4 / CeO2-MD.
[0114] Example 12 Synthesis of antibacterial nanocomposite materials by template method
[0115] 0.2L 8.68g / mol Ce(NO3)3 solution and 4g g-C3N4 synthesized in Example 1 (ie, the molar ratio of g-C3N4 to Ce is 0.10:1) were added according to the synthesis method in Example 7 to prepare g-C3N4 / CeO2-MD.
[0116] Example 13 Synthesis of antibacterial nanocomposite materials by template method
[0117] It is basically the same as Example 9, except that after collection, it is calcined at 500°C for 3h in a muffle furnace to obtain g-C3N4 / CeO2-MD.
[0118] Example 14 Synthesis of antibacterial nanocomposite materials by template method
[0119] It is basically the same as Example 9, except that after collection, it is calcined at 600°C in a muffle furnace for 1 hour to obtain g-C3N4 / CeO2-MD.
[0120] Example 15 Preparation of antibacterial nanoparticle-chitosan suspension
[0121] This embodiment provides a method for preparing a suspension by combining the antibacterial nanocomposite material synthesized in the above embodiments 2 to 14 with chitosan. The following takes the g-C3N4 / CeO2-HT synthesized in embodiment 3 as an example to provide a specific implementation method:
[0122] 1.00 g of chitosan (CS) and 0.01 g of g-C3N4 / CeO2-HT synthesized in Example 3 (i.e., the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.01) were weighed and mixed to obtain a mixture; the mixture was then placed in 100 mL of 1% (v / v) acetic acid solution for dissolution, and a magnetic stirrer was used to stir at a speed of 100 rpm to accelerate the dissolution, and the mixture was completely dissolved by stirring for 24 hours to obtain a suspension.
[0123] Example 16 Preparation of antibacterial nanoparticle-chitosan suspension
[0124] It is basically the same as Example 15, except that 1.00 g of chitosan and 0.1 g of g-C3N4 / CeO2-HT synthesized in Example 3 (ie, the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.1) are weighed and mixed to obtain a suspension.
[0125] Example 17 Preparation of antibacterial nanoparticle-chitosan suspension
[0126] It is basically the same as Example 15, except that 1.00 g of chitosan and 0.2 g of g-C3N4 / CeO2-HT synthesized in Example 3 (ie, the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.2) are weighed and mixed to obtain a suspension.
[0127] Example 18 Preparation of antibacterial nanoparticle-chitosan suspension
[0128] It is basically the same as Example 15, except that 1.00 g of chitosan and 0.5 g of g-C3N4 / CeO2-HT synthesized in Example 3 (ie, the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.5) are weighed and mixed to obtain a suspension.
[0129] Example 19 Preparation of antibacterial nanoparticle-chitosan suspension
[0130] It is basically the same as Example 15, except that 1.00 g of chitosan and 0.01 g of g-C3N4 / CeO2-MD synthesized in Example 11 (i.e., the mass ratio of CS to g-C3N4 / CeO2-MD is 1:0.01) are weighed and mixed to obtain a suspension.
[0131] Example 20 Preparation of antibacterial nanoparticle-chitosan suspension
[0132] It is basically the same as Example 19, except that 1.00 g of chitosan and 0.1 g of g-C3N4 / CeO2-MD synthesized in Example 11 (i.e., the mass ratio of CS to g-C3N4 / CeO2-MD is 1:0.1) are weighed and mixed to obtain a suspension.
[0133] Example 21 Preparation of antibacterial nanoparticle-chitosan suspension
[0134] It is basically the same as Example 19, except that 1.00 g of chitosan and 0.2 g of g-C3N4 / CeO2-MD synthesized in Example 11 (i.e., the mass ratio of CS to g-C3N4 / CeO2-MD is 1:0.2) are weighed and mixed to obtain a suspension.
[0135] Example 22 Preparation of antibacterial nanoparticle-chitosan suspension
[0136] It is basically the same as Example 19, except that 1.00 g of chitosan and 0.5 g of g-C3N4 / CeO2-MD synthesized in Example 11 (i.e., the mass ratio of CS to g-C3N4 / CeO2-MD is 1:0.5) are weighed and mixed to obtain a suspension.
[0137] Example 23 Preparation of antibacterial nanoparticle-chitosan film
[0138] Take 100.00g of the suspension obtained in any one of Examples 15 to 22, pour it into a box of 10cm×10cm×1cm, and dry it in a 45°C oven until it forms a film (generally 24 to 48 hours) to obtain a film of antibacterial nanoparticles-chitosan. When the suspension used is obtained by any one of Examples 15 to 18 (i.e., the antibacterial nanoparticles used are g-C3N4 / CeO2-HT), the corresponding film obtained is recorded as g-C3N4 / CeO2-HT film; when the suspension used is obtained by any one of Examples 19 to 22 (i.e., the antibacterial nanoparticles used are g-C3N4 / CeO2-MD), the corresponding film obtained is recorded as g-C3N4 / CeO2-MD film.
[0139] Application Example 1 Characterization of antibacterial nanocomposites and antibacterial nanoparticle-chitosan films
[0140] 1. Characterization of antibacterial nanocomposites
[0141] 1. Fourier transform infrared spectroscopy (FTIR)
[0142] (1) Characterization methods
[0143] The composite materials (i.e., g-C3N4, CeO2, g-C3N4 / CeO2-HT prepared in Examples 2 to 8, and g-C3N4 / CeO2-MD prepared in Examples 9 to 14) were characterized by FTIR technology. The main operation steps were as follows: 1 mg of sample powder of the composite material was weighed and mixed with 100 mg of KBr, and then ground and pressed into a tablet. The wavelength range of 400 to 4000 cm -1 Measurements are performed within the sample to analyze the characteristic peaks of the composite material.
[0144] (2) Characterization results
[0145] The FTIR spectra of each composite material are shown in Figure 1 As shown in A, CeO2 is at 400cm -1 ~600cm -1 There are absorption bands in the wavelength range, which are caused by Ce-O stretching vibration; g-C3N4 at 806cm -1 、1240cm -1 、1322cm -1 、1402cm -1 and 1563cm -1 There are characteristic peaks, which are related to the stretching of CN; the characteristic peaks of CeO2 and g-C3N4 can be observed simultaneously in the spectra of g-C3N4 / CeO2-HT prepared in Example 3 and g-C3N4 / CeO2-MD prepared in Example 11. The characteristic peaks of CeO2 and g-C3N4 can also be observed simultaneously in the FTIR spectra of g-C3N4 / CeO2-HT prepared in Example 2 and Examples 4 to 8, and g-C3N4 / CeO2-MD prepared in Examples 9 to 10 and Examples 12 to 14.
[0146] The above results indicate that the present invention successfully synthesized the antibacterial nanocomposite material of CeO2 modified by g-C3N4 using both the hydrothermal method and the template method.
[0147] 2. Ultraviolet visible diffuse reflectance spectroscopy (UV / Vis-DRS)
[0148] (1) Characterization methods
[0149] The composite materials (i.e. g-C3N4, CeO2, g-C3N4 / CeO2-HT prepared in Examples 2 to 8 and g-C3N4 / CeO2-MD prepared in Examples 9 to 14) were characterized by UV / Vis-DRS technology, with a scanning wavelength range of 200 to 900 nm and BaSO4 as a reference material. The width of the optical band gap of the corresponding composite materials was calculated by formula (1), and the electronic structures of g-C3N4, CeO2, g-C3N4 / CeO2-HT and g-C3N4 / CeO2-MD were evaluated based on this, and the light absorption capacity of each composite material was judged. The smaller the width of the optical band gap, the wider the light absorption range of the material and the stronger the light absorption capacity.
[0150] Formula (1): Eg = 1240 / λ onset ;
[0151] Where Eg is the optical band gap of the composite material (unit: eV); λ onset is the wavelength of the incident light wave of the composite material (unit: nm).
[0152] The wavelength of the incident light wave of the composite material is obtained by drawing a Tauc relationship diagram of the band gap of the prepared photocatalyst based on the Kubelka-Munk function formula (i.e., formula (2)) and the extended tangent.
[0153] Formula (2): (αhv)^(1 / 2)=A(hv-Eg);
[0154] Among them, hv is the incident photon energy; α is the light absorption coefficient; A is a constant.
[0155] (2) Characterization results
[0156] The UV / Vis-DRS spectra and Tauc relationship diagrams of each composite material are shown in Figure 1 As shown in Figures B and C, the absorption starting wavelength of g-C3N4 is about 470nm, and its optical band gap is 2.63eV; the absorption starting wavelength of CeO2 is about 408nm, and its optical band gap is 3.04eV; the absorption starting wavelengths of g-C3N4 / CeO2-HT prepared in Example 3 and g-C3N4 / CeO2-MD prepared in Example 11 are 478nm and 474nm, respectively, and their respective optical band gaps are 2.59eV and 2.61eV, respectively, which are narrower than the optical band gap of CeO2, indicating that the energy required for electrons to transition from the valence band to the conduction band is reduced. The UV / Vis-DRS test results of g-C3N4 / CeO2-HT prepared in Example 2, Examples 4 to 8, and g-C3N4 / CeO2-MD prepared in Examples 9 to 10 and Examples 12 to 14 also show that they have a narrower optical band gap than CeO2.
[0157] The above results show that, compared with CeO2, the antibacterial nanocomposite material prepared by the hydrothermal method and the template method of the present invention has stronger light absorption ability and a wider light absorption range, and can better utilize visible light with a wider wavelength range (wavelength>400nm).
[0158] 2. Characterization of antibacterial nanoparticle-chitosan film
[0159] 1. Scanning Electron Microscope (SEM)
[0160] (1) Characterization methods
[0161] The surface morphology and element distribution of the CS / g-C3N4 / CeO2-HT film prepared in Example 23 were detected by SEM. The specific steps are as follows: each CS / g-C3N4 / CeO2-HT film was coated on a conductive adhesive, purged with nitrogen, and subjected to gold spraying. Then, they were placed in a scanning electron microscope for testing at an acceleration voltage of 20 kV. The surface morphology and element distribution of each CS / g-C3N4 / CeO2-HT film were observed and photographed.
[0162] (2) Characterization results
[0163] like Figure 2 As shown in A to D in the figure, the surface morphology of CS / g-C3N4 / CeO2-HT films prepared with different mass ratios of chitosan and antibacterial nanocomposites is clearly visible. The surface is flat and dense as a whole without cracks. The raised particles are g-C3N4 / CeO2-HT. It can be seen that with the increase in the amount of g-C3N4 / CeO2-HT, more particles are attached to the surface of the film, making the surface of the film gradually uneven and with slight agglomeration, but the overall distribution of the particles is relatively uniform and sparse. At the same time, some large lumps can be observed on the surface of the film, which is caused by the chitosan wrapping of g-C3N4 / CeO2-HT.
[0164] like Figure 3 As shown in A to D in the figure, the CS / g-C3N4 / CeO2-HT film surface prepared with different mass ratios of chitosan and antibacterial nanocomposites has four elements of C, N, O and Ce, indicating that the molecular structure of the CS / g-C3N4 / CeO2-HT film is composed of four elements of C, N, O and Ce, and the added chitosan material does not introduce other elements; with the increase of the amount of g-C3N4 / CeO2-HT, the distribution of C and O elements on the surface of the CS / g-C3N4 / CeO2-HT film is wider and relatively dense, the N element is relatively sparse, and the Ce element is more widely and denser with the increase of the catalyst mass.
[0165] 2. High-resolution field emission transmission electron microscopy (HRTEM)
[0166] (1) Characterization methods
[0167] The microscopic morphology of the CS / g-C3N4 / CeO2-MD film prepared in Example 23 was observed by HRTEM. The specific steps were as follows: 0.04 g of each CS / g-C3N4 / CeO2-HT film was uniformly dispersed in 40 mL of anhydrous ethanol with the assistance of ultrasound, and then dropwise added onto a copper grid sample mesh coated with a carbon layer to obtain HR-TEM images, observe the deeper microscopic morphological structure of the nanoparticle-chitosan film material, and measure the spacing of the lattice fringes using Digital micrograph 3 software.
[0168] (2) Characterization results
[0169] like Figure 4 As shown in A and B, the g-C3N4 / CeO2-MD in the CS / g-C3N4 / CeO2-MD film prepared by Example 22 is spherical particles, and the plane lattice fringes of CeO2 are obvious (indicated by the arrow). After measurement, there are two lattice fringes of d=0.312nm and d=0.270nm, which are typical (111) and (200) crystal plane features of CeO2. It can also be clearly seen that the CS / g-C3N4 / CeO2-MD containing CeO2 is wrapped in chitosan macromolecules. Similar morphology can also be observed in the HRTEM images of the CS / g-C3N4 / CeO2-MD films prepared by Examples 19 to 21.
[0170] Application Example 2 Evaluation of Antibacterial and Biofilm Removal and Inhibition Performance
[0171] 1. Evaluation of antibacterial properties of antibacterial nanocomposites
[0172] 1. Detection method
[0173] After conventional sterilization treatment, 0.02 g of g-C3N4 / CeO2-HT prepared in Examples 2 to 6 and g-C3N4 / CeO2-MD prepared in Examples 7 to 10 were taken and placed in quartz rings, and then placed in different quartz culture dishes. Then, 3 mL of Staphylococcus aureus (S. aureus) 10071 bacterial solution (containing 5×10 4 CFU / mL), then add 27mL of normal saline, mix well, cover the culture dish, place on a magnetic stirrer, cover with a light-shielding cover, and then react (adsorption-desorption) in the dark for 30 minutes, then turn on the ultraviolet light for 30 minutes, and react for a total of 60 minutes.
[0174] 100 μL of sample was taken from each culture dish at 0 min and 30 min after UV irradiation, and the sample was evenly spread on mannitol sodium chloride agar medium and marked, then inverted and placed in a 37°C biochemical incubator for 24 h. After visible colonies grew, the plate was taken out for counting and recording, and the antibacterial rate of each antibacterial nanocomposite material against Staphylococcus aureus (S. aureus) 10071 was calculated according to formula (3).
[0175] Formula (3):
[0176] Among them, R represents the antibacterial rate, N0 represents the number of colonies in the sample irradiated with ultraviolet light for 0 min, and N t It indicates the number of colonies in the sample irradiated with UV light for 30 minutes.
[0177] 2. Test results
[0178] like Figure 5 As shown in A, the g-C3N4 / CeO2-HT prepared in Examples 2 to 6 can inhibit the growth of Staphylococcus aureus (S.aureus) 10071, and the antibacterial rates are 57.87%, 71.43%, 67.08%, 59.66% and 50.31% respectively, among which the g-C3N4 / CeO2-HT in Example 3 has the highest antibacterial rate, indicating that the optimal mass ratio of g-C3N4 to CeO2 for synthesizing antibacterial nanocomposites by hydrothermal method is 1:1. .
[0179] like Figure 5 As shown in B, the g-C3N4 / CeO2-MD prepared in Examples 7 to 10 can inhibit the growth of Staphylococcus aureus (S.aureus) 10071, and the antibacterial rates are 58.45%, 64.61%, 53.27% and 47.14%, respectively. Among them, the g-C3N4 / CeO2-MD prepared in Example 11 has the highest antibacterial rate, indicating that the optimal molar ratio of Ce to g-C3N4 for synthesizing antibacterial nanocomposites using the template method is 0.08:1.
[0180] 2. Evaluation of the antibacterial properties of antibacterial nanoparticle-chitosan films
[0181] 1. Bacterial culture and antibacterial rate determination under no light conditions
[0182] Under light-free conditions, the CS / g-C3N4 / CeO2-MD film prepared in Example 23 (the suspension used was prepared in Example 20) was cut into long strips and placed on a glass slide; 100 μL of the bacterial solution of Escherichia coli (O78) and Staphylococcus aureus (S. aureus) 10071 or 10008 cultured to the logarithmic growth phase was added dropwise to the CS / g-C3N4 / CeO2-MD film as a treatment group, and a blank glass slide with the corresponding bacterial solution added was used as a blank group, and then placed in a biochemical incubator for culture for 24 hours.
[0183] Take out the culture dish, use a pipette to add 1900 μL of physiological saline to wash the bacterial solution on the film, dilute the bacterial solution and spread it on the plate using the dilution plate method (tryptone soy broth agar medium for Escherichia coli, mannitol sodium chloride agar medium for Staphylococcus aureus), and dilute the bacterial solution of Escherichia coli to 10 -4 times (the colony count of the blank group was between 100 and 300), Staphylococcus aureus was diluted to 10 -5 times, then inverted and placed in a biochemical incubator for culture (Escherichia coli culture for 12 hours, Staphylococcus aureus culture for 24 hours).
[0184] After the culture was completed, the plates were taken out for counting and recording, and the antibacterial rate of the antibacterial nanoparticle-chitosan film against each bacteria was calculated according to formula (4).
[0185] Formula (4): R=(N0-N K )÷N0×100%;
[0186] Among them, R represents the inhibition rate, N0 represents the number of colonies in the blank group, and N k The colony numbers represent the treatment groups.
[0187] 2. Bacterial culture and antibacterial rate determination under ultraviolet light conditions
[0188] The operation steps are basically the same as those under the no-light conditions, with the only difference being that: under the no-light conditions, the CS / g-C3N4 / CeO2-MD film prepared in Example 23 (the suspension used is prepared in Example 20) is cut into long strips and placed on a glass slide; 100 μL of the bacterial solution of Escherichia coli (O78) and Staphylococcus aureus (S. aureus) 10071 or 10008 cultured to the logarithmic growth phase is added dropwise to the CS / g-C3N4 / CeO2-MD film as the treatment group, and a blank glass slide with the corresponding bacterial solution added is used as the blank group. After irradiation with ultraviolet light for 3 minutes, it is placed in a biochemical incubator and cultured for 24 hours.
[0189] 3. Bacterial culture and antibacterial rate determination under normal visible light conditions
[0190] The operation steps are basically the same as those under no light conditions, with the only difference being that: under normal visible light conditions, the CS / g-C3N4 / CeO2-HT film prepared in Example 23 (the suspension used is prepared by Examples 15 to 18) is cut into long strips and placed on a glass slide, and 0.5 g of g-C3N4 / CeO2-HT prepared in Example 3 is evenly spread on the glass slide; 100 μL of the bacterial solution of Escherichia coli (O78) and Staphylococcus aureus (S. aureus) 10071 or 10008 cultured to the logarithmic growth phase is respectively added dropwise to each CS / g-C3N4 / CeO2-HT film or the glass slide with g-C3N4 / CeO2-HT as the treatment group, and a blank glass slide with the corresponding bacterial solution is used as the blank group, and then placed in a biochemical incubator for culture for 24 hours.
[0191] 4. Test results
[0192] like Figure 6 As shown in A, regardless of the presence or absence of ultraviolet light irradiation, the antibacterial rate of the CS / g-C3N4 / CeO2-MD film prepared in Example 23 (the suspension used was prepared by Example 20) against Escherichia coli was 100%, and the Escherichia coli could be completely killed; under the condition of no ultraviolet light irradiation, the antibacterial rate of the CS / g-C3N4 / CeO2-MD film prepared in Example 23 (the suspension used was prepared by Example 20) against Staphylococcus aureus 10071 was 33.03%, and the antibacterial rate against Staphylococcus aureus 10008 was 94.60%; since g-C3N4 / CeO2-MD has photocatalytic properties, after increasing ultraviolet light irradiation, the antibacterial performance of the CS / g-C3N4 / CeO2-MD film prepared in Example 23 (the suspension used was prepared by Example 20) against the two types of Staphylococcus aureus was significantly enhanced, and the inhibition rates were increased to 99.10% and 96.00%, respectively. The CS / g-C3N4 / CeO2-MD films prepared using the suspensions in Examples 19 and 21 to 22 also have similar antibacterial properties.
[0193] like Figure 6As shown in B, under normal lighting conditions, the antibacterial rate of the CS / g-C3N4 / CeO2-HT film prepared in Example 23 (the suspension used was prepared by Examples 15 to 18) against Escherichia coli was 100%, which could completely kill Escherichia coli; the antibacterial rate of the CS / g-C3N4 / CeO2-HT film prepared in Example 23 (the suspension used was prepared by Examples 15 to 18) against Staphylococcus aureus was above 40%, wherein the suspension used was the CS / g-C3N4 / CeO2-HT film prepared in Example 15 (CS and g-C3N4 / CeO2-HT The mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.01) has the highest antibacterial rate against Staphylococcus aureus 10071, reaching 96.03%, followed by CS / g-C3N4 / CeO2-HT film (the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.5) whose suspension is composed of Example 18, with an antibacterial rate of 95.27%; the suspension used is CS / g-C3N4 / CeO2-HT film (the mass ratio of CS to g-C3N4 / CeO2-HT is 1:0.5) prepared by Example 18, with the highest antibacterial rate against Staphylococcus aureus 10008, reaching 100%.
[0194] The above results show that the antibacterial nanoparticle-chitosan film provided by the present invention has excellent antibacterial properties and significantly inhibits the growth of Gram-positive bacteria and Gram-negative bacteria. Adjusting the lighting mode can further enhance its antibacterial effect.
[0195] 2. Evaluation of biofilm inhibition and removal performance
[0196] 1. Biofilm inhibition simulation experiment
[0197] (1) Direct addition method
[0198] In daily application scenarios, the use of bactericides is often involved. In order to evaluate the performance of antibacterial nanocomposites in inhibiting the formation of bacterial biofilms, a simulation experiment was conducted using the direct sample addition method, which is equivalent to directly spraying bactericides without treating the bacterial growth environment in the actual operation process, thereby inhibiting the formation of biofilms. The specific steps are as follows:
[0199] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600The value was adjusted to 0.001, and then added to a sterile 96-well plate at 200 μL / well, and then g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL, g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL, silver nanoparticles (Ag nanoparticles, as a positive control) with a final concentration of 0 mg / L, 100 mg / L or 1000 mg / L, or 8 kinds of antibacterial nanoparticle-chitosan suspensions prepared in Examples 15 to 22 were added to the culture wells containing the bacterial solution at 100 μL / well as the experimental group, and the original culture wells without further treatment were used as the blank control group, and cultured at 37°C for 24 h.
[0200] (2) Direct addition method + UV irradiation
[0201] Considering the photocatalytic performance of the antibacterial nanocomposites, the effect of light on the performance of the antibacterial nanocomposites in inhibiting the formation of bacterial biofilms was further evaluated, and ultraviolet light irradiation was combined with the direct addition method. The specific steps are as follows:
[0202] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600 The value was adjusted to 0.001, and then 200 μL / well was added to a sterile 96-well plate. Then, g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL and g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL were added to the culture wells containing the bacterial solution at 100 μL / well as the experimental group, and the original culture wells without further treatment were used as the blank control group. They were irradiated with ultraviolet light for 3 minutes and then cultured at 37°C for 24 hours.
[0203] (3) Direct addition method + visible light irradiation
[0204] Considering the photocatalytic performance of antibacterial nanocomposites, the effect of light on the performance of antibacterial nanocomposites in inhibiting bacterial biofilm formation was further evaluated, and visible light irradiation was combined with the direct addition method. The specific steps are as follows:
[0205] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600The value was adjusted to 0.001, and then added to a sterile 96-well plate at 200 μL / well, and then g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL, g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL, silver nanoparticles (Ag nanoparticles, as a positive control) with a final concentration of 0 mg / L, 100 mg / L or 1000 mg / L, or 8 kinds of antibacterial nanoparticle-chitosan suspensions prepared in Examples 15 to 22 were added to the culture wells containing the bacterial solution at 100 μL / well as the experimental group, and the original culture wells without further treatment were used as the blank control group, irradiated with visible light for 3 minutes, and then cultured at 37°C for 24 hours.
[0206] 2. Biofilm removal simulation experiment
[0207] (1) De-pegar method
[0208] In order to evaluate the performance of antibacterial nanocomposites in removing mature bacterial biofilms in daily application scenarios, a simulation experiment was conducted using the removal and addition method, which is equivalent to first removing the growth environment of bacteria and their biofilms with water, leaving the mature biofilms on the surface, and then spraying the bactericide on them to remove the mature biofilms. The specific steps are as follows:
[0209] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600 The value was adjusted to 0.001, and then 200 μL / well was added to a sterile 96-well plate and cultured at 37°C for 24 hours; after the culture, the culture medium in the 96-well plate was discarded, and g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL, g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL, silver nanoparticles (Ag nanoparticles, as a positive control) with a final concentration of 0 mg / L, 100 mg / L or 1000 mg / L, or 8 kinds of antibacterial nanoparticle-chitosan suspensions prepared according to the methods of Examples 15 to 22 were added to the original culture wells at 100 μL / well as experimental groups, and the original culture wells without further treatment were used as blank control groups, and cultured at 37°C for another 24 hours.
[0210] (2) De-peptide method + UV irradiation
[0211] Considering the photocatalytic performance of antibacterial nanocomposites, the effect of light on the performance of antibacterial nanocomposites in removing mature bacterial biofilms was further evaluated, and ultraviolet light irradiation was combined with the de-plasma addition method. The specific steps are as follows:
[0212] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600 The value was adjusted to 0.001, and 200 μL / well was added to a sterile 96-well plate and cultured at 37°C for 24 hours. After the culture, the culture medium in the 96-well plate was discarded, and g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL and g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL were added to the original culture wells at 100 μL / well as the experimental group, and the original culture wells without further treatment were used as the blank control group. They were irradiated with ultraviolet light for 3 minutes and cultured at 37°C for another 24 hours.
[0213] (3) De-peptide method + visible light irradiation
[0214] Considering the photocatalytic performance of antibacterial nanocomposites, the effect of light on the performance of antibacterial nanocomposites in removing mature bacterial biofilms was further evaluated, and visible light irradiation was combined with the de-plasma method. The specific steps are as follows:
[0215] Take the bacterial suspension of Staphylococcus aureus (S. aureus) 10071 or 10008 cultured overnight at 37°C and 180 r / min, dilute it and transfer it to fresh mannitol sodium chloride agar medium, culture it to the logarithmic growth phase, and adjust the OD of the bacterial suspension. 600 The value was adjusted to 0.001, and then 200 μL / well was added to a sterile 96-well plate and cultured at 37°C for 24 hours; after the culture, the culture medium in the 96-well plate was discarded, and g-C3N4 / CeO2-HT prepared in Example 3 with a final concentration of 10 g / μL, g-C3N4 / CeO2-MD prepared in Example 11 with a final concentration of 10 g / μL, silver nanoparticles with a final concentration of 0 mg / L, 100 mg / L or 1000 mg / L (Ag nanoparticles were used as a positive control), or 8 kinds of antibacterial nanoparticle-chitosan suspensions prepared according to the methods of Examples 15 to 22 were added to the original culture wells at 100 μL / well as the experimental group, and the original culture wells without further treatment were used as the blank control group, irradiated with visible light for 3 minutes, and cultured at 37°C for another 24 hours.
[0216] 3. Determination of the total amount and removal rate of biofilm
[0217] The crystal violet (CV) method was used to determine the total amount of bacterial biofilm in the culture products under different experimental conditions (direct sample addition method, direct sample addition method + ultraviolet irradiation, direct sample addition method + visible light irradiation, sample addition method without culture, sample addition method without culture + ultraviolet irradiation, and sample addition method without culture + visible light irradiation). The specific steps are as follows:
[0218] After the incubation, each well was washed three times with PBS buffer to remove surface impurities and floating bacteria, and then stained with 0.01% sterile crystal violet solution for 15 minutes. After staining, it was washed twice with sterile water, and then 95% ethanol was added to elute the crystal violet, and the eluate was collected. 125 μL of the eluate was placed in a new ELISA plate, and the absorbance (OD value) of each well was measured at 540 nm using an ELISA instrument, and the biofilm clearance rate was calculated using formula (5).
[0219] Formula (5): Clearance rate (%) = (ODc-ODs) / ODc×100%;
[0220] Among them, ODs represents the OD value of the experimental group; ODc represents the OD value of the blank control group.
[0221] 4. Test results
[0222] like Figure 7As shown in A and B in the figure, under the direct sample addition condition, the removal rates of the g-C3N4 / CeO2-HT prepared in Example 3 against the mature biofilms of Staphylococcus aureus (S. aureus) 10071 and 10008 were 56.33% and 36.00%, respectively, and the removal rates of the g-C3N4 / CeO2-MD prepared in Example 11 against the mature biofilms of Staphylococcus aureus (S. aureus) 10071 and 10008 were 69.23% and 65. .45%; under the conditions of direct sample addition + ultraviolet irradiation, the removal rates of the g-C3N4 / CeO2-HT prepared in Example 3 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 0% and 29.09%, respectively, and the removal rates of the g-C3N4 / CeO2-MD prepared in Example 11 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 66.50% and 49.0 9%; under the condition of no culture addition, the removal rates of g-C3N4 / CeO2-HT prepared in Example 3 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 39.45% and 43.64%, respectively, and the removal rates of g-C3N4 / CeO2-MD prepared in Example 11 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 71.96% and 50.55%, respectively; Under the conditions of de-plasma addition + ultraviolet light irradiation, the removal rates of the g-C3N4 / CeO2-HT prepared in Example 3 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 9.43% and 52.73%, respectively. The removal rates of the g-C3N4 / CeO2-MD prepared in Example 11 on the mature biofilms of Staphylococcus aureus (S.aureus) 10071 and 10008 were 70.72% and 66.91%, respectively.
[0223] like Figure 8As shown in A and B in the figure, under the direct sample addition condition, the clearance rates of the g-C3N4 / CeO2-HT of Example 3, the g-C3N4 / CeO2-MD of Example 11 and the 8 antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S. aureus) 10071 were 30.77%, 45.41%, 31.02%, 16.13%, 0%, 0%, 40.69%, 40.94%, 39.95% and 37.97% respectively. %; Under the conditions of direct sample addition + visible light irradiation, the clearance rates of g-C3N4 / CeO2-HT in Example 3, g-C3N4 / CeO2-MD in Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S.aureus) 10071 were 25.56%, 25.56%, 15.63%, 7.20%, 0%, 0%, 26.05%, 21.09%, 22.33% and 23.33%, respectively.
[0224] like Figure 8 As shown in Figures C and D, under direct sample addition conditions, the clearance rates of g-C3N4 / CeO2-HT of Example 3, g-C3N4 / CeO2-MD of Example 11 and 8 antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S. aureus) 10008 were 55.27%, 55.64%, 53.45%, 53.82%, 48.36%, 0%, 53.45%, 45.09%, 59.27% and 53.46%, respectively. 5%; under the conditions of direct sample addition + visible light irradiation, the clearance rates of g-C3N4 / CeO2-HT in Example 3, g-C3N4 / CeO2-MD in Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S.aureus) 10008 were 45.45%, 42.55%, 28.36%, 17.69%, 0%, 0%, 50.91%, 50.91%, 45.45% and 48.36%, respectively.
[0225] like Fig. 9As shown in A and B in the figure, under the condition of no addition of sample, the removal rates of g-C3N4 / CeO2-HT of Example 3, g-C3N4 / CeO2-MD of Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S.aureus) 10071 were 63.77%, 67.49%, 57.57%, 61.29%, 29.28%, 0%, 66.50%, 67.25%, 65.26% and 61.29%, respectively. ; Under the conditions of de-peptide + visible light irradiation, the removal rates of g-C3N4 / CeO2-HT in Example 3, g-C3N4 / CeO2-MD in Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S.aureus) 10071 were 65.26%, 55.58%, 51.04%, 54.84%, 51.86%, 0%, 54.84%, 55.09%, 55.58% and 49.88%, respectively.
[0226] like Fig. 9 As shown in Figures C and D, under the condition of no culture, the clearance rates of g-C3N4 / CeO2-HT of Example 3, g-C3N4 / CeO2-MD of Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S. aureus) 10008 were 57.45%, 52.36%, 54.18%, 53.09%, 47.27%, 5.09%, 58.55%, 56.00%, 56.73% and 57.00%, respectively. 9%; under the conditions of de-peptide + visible light irradiation, the clearance rates of g-C3N4 / CeO2-HT of Example 3, g-C3N4 / CeO2-MD of Example 11 and 8 kinds of antibacterial nanoparticle-chitosan suspensions on the mature biofilm of Staphylococcus aureus (S.aureus) 10008 were 49.45%, 17.09%, 46.54%, 40.00%, 54.55%, 0%, 36.73%, 38.55%, 40.73% and 45.82%, respectively.
[0227] like Fig.10As shown in A and B in the figure, under direct sample addition conditions, the removal rates of the mature biofilm of Staphylococcus aureus (S. aureus) 10071 by the Ag nanoparticles (positive control) with a final concentration of 10 mg / L, 100 mg / L and 1000 mg / L were 26.42%, 44.00% and 43.17%, respectively; under direct sample addition + visible light irradiation conditions, the removal rates of the mature biofilm of Staphylococcus aureus (S. aureus) 10071 by the Ag nanoparticles with a final concentration of 10 mg / L, 100 mg / L and 1000 mg / L were 55.42%, 64.58% and 49.17%, respectively. Fig.10 As shown in Figures C and D, under the de-plasma-added conditions, the clearance rates of Ag nanoparticles with final concentrations of 10 mg / L, 100 mg / L and 1000 mg / L on the mature biofilm of Staphylococcus aureus (S. aureus) 10071 were 30.00%, 33.67% and 34.83%, respectively; under the de-plasma-added + visible light irradiation conditions, the clearance rates of Ag nanoparticles with final concentrations of 10 mg / L, 100 mg / L and 1000 mg / L on the mature biofilm of Staphylococcus aureus (S. aureus) 10071 were 49.25%, 53.83% and 32.17%, respectively.
[0228] The above results show that the antibacterial nanocomposite provided by the present invention can effectively inhibit and remove biofilms generated by bacteria, especially mature biofilms, and the removal effect is significantly better than the commonly used bactericides (nano-Ag particles) in the prior art, among which the antibacterial nanocomposite synthesized by the template method has better performance. In addition, in order to provide new antibacterial materials, the present invention also prepares a suspension for preparing a film by combining the antibacterial nanocomposite with chitosan. The solution also has the function of inhibiting and removing bacterial biofilms, but the amount of chitosan used and the irradiation of visible light have a slight effect on this function, and in actual production and use, only adaptive adjustment and optimization are required.
[0229] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an antibacterial nanocomposite material, characterized in that: The antibacterial nanocomposite material is synthesized by using graphite phase carbon nitride and cerium salt through a hydrothermal method or a template method; The hydrothermal method comprises the following steps: after the graphite phase carbon nitride and cerium dioxide are fully dispersed, a sufficient hydrothermal reaction is carried out in a closed container to obtain; the mass ratio of the graphite phase carbon nitride to the cerium dioxide is 1: (0.5-3); the conditions of the hydrothermal reaction include: the temperature is 100°C-150°C; The template method comprises the following steps: fully combining the graphite phase carbon nitride with a cerium nitrate solution, separating the solid from the liquid, collecting the liquid, removing the solvent of the liquid to obtain a precipitate, and fully calcining the precipitate to obtain the graphite phase carbon nitride; the molar ratio of cerium in the cerium nitrate to the graphite phase carbon nitride is (0.04-0.10):1; the calcination conditions include: the calcination temperature is 500°C-600°C.
2. The preparation method according to claim 1, characterized in that: The conditions of the hydrothermal reaction also include: the reaction time is 16h to 20h.
3. The preparation method according to claim 1, characterized in that: The calcination conditions also include: the calcination time is 1 hour to 3 hours.
4. The antibacterial nanocomposite material obtained according to the preparation method according to any one of claims 1 to 3.
5. Use of the antibacterial nanocomposite material according to claim 4 in in vitro bacteriostasis and / or in vitro bactericidal activity.
6. Use of the antibacterial nanocomposite material according to claim 4 in the preparation of antibacterial products.
7. Use of the antibacterial nanocomposite material according to claim 4 in the preparation of products for removing and / or inhibiting bacterial biofilm.
8. An antibacterial composition, characterized in that The invention comprises the antibacterial nanocomposite material as claimed in claim 4 and chitosan.
9. The antibacterial composition according to claim 8, characterized in that The mass ratio of the chitosan to the antibacterial nanocomposite material according to claim 4 is 1:(0.01-0.5).
10. An antibacterial agent, characterized in that It comprises the antibacterial nanocomposite material according to claim 4 or the antibacterial composition according to any one of claims 8 to 9.
Citation Information
Cited By
Cerium oxide / piezoelectric material composite nano-enzyme for antifouling coating as well as preparation method and application of cerium oxide / piezoelectric material composite nano-enzyme
CN121797381A